Echovirus-30 infection alters host proteins in lipid rafts at the cerebrospinal fluid barrier in vitro - Wiatr, Marie; Staubach, Simon; Figueiredo, Ricardo; Stump-Guthier, Carolin; Ishikawa, Hiroshi; Schwerk, Christian; Schroten, Horst; Hanisch, Franz-Georg; Rudolph, Henriette; Tenenbaum, Tobias (Microorganisms, 2020)
Echovirus-30 (E-30) is a non-polio enterovirus responsible for meningitis outbreaks in children worldwide. To gain access to the central nervous system (CNS), E-30 first has to cross the blood-brain barrier (BBB) or the blood-cerebrospinal fluid barrier (BCSFB). E-30 may use lipid rafts of the host cells to interact with and to invade the BCSFB. To study enteroviral infection of the BCSFB, an established in vitro model based on human immortalized brain choroid plexus papilloma (HIBCPP) cells has been used. Here, we investigated the impact of E-30 infection on the protein content of the lipid rafts at the BCSFB in vitro. Mass spectrometry analysis following E-30 infection versus uninfected conditions revealed differential abundancy in proteins implicated in cellular adhesion, cytoskeleton remodeling, and endocytosis/vesicle budding. Further, we evaluated the blocking of endocytosis via clathrin/dynamin blocking and its consequences for E-30 induced barrier disruption. Interestingly, blocking of endocytosis had no impact on the capacity of E-30 to induce loss of barrier properties in HIBCPP cells. Altogether, these data highlight the impact of E-30 on HIBCPP cells microdomain as an important factor for host cell alteration.